(untitled) (Global Journal of Management and Business Research, 2017)
Due to its dynamic and emergent nature, the effectiveness of social media as a marketing communication channel has presented many challenges for marketers. It is considered to be different to traditional marketing channels. Many organizations are investing in their social media presence because they appreciate the need to engage in existing social media conversations in order to build their brand equity. Social Medias are increasingly replacing traditional media, and more consumers are using them as a source of information about products, services and brands. On the other hand, brand equity is considered as a powerful mechanism to create the sustainable competitive advantage for the organizational concern. Thus, this study examined the research problem of whether the social media marketing (SMM) impacts on brand equity in Travel & Tourism Industry (TTI) in Sri Lanka. The objective of this study is to identify the impact of SMM on brand equity in Sri Lankan Travel& Tourism Industry (TTI). Furthermore, the conceptual model has been developed to link SMM and brand equity.